Extraction of ACE-inhibiting dipeptides from protein hydrolysates using porous carbon materials - Hippauf, Felix; Lunow, Diana; Borchardt, Lars; Henle, Thomas; Kaskel, Stefan (Carbon, 2014)
This study reports on the extraction of strongly angiotensin-converting enzyme (ACE) inhibiting dipeptides from protein hydrolysates obtained by enzymatic proteolysis. Several dipeptides with different ACE inhibitory activities and hydrophobicities were investigated regarding to their adsorption affinity on commercially available activated carbon material Norit DLC Super 50. This porous carbon exhibits extremely high adsorption capacities for the strongest ACE inhibitor Ile-Trp (IC50 = 0.7 μM) of 726 mg/g as well as fast adsorption kinetics due to its micropore structure and small particle size. The filling of the pores was monitored by N2- physisorption revealing that complete pore filling occurred and Ile-Trp adsorption was only limited by the specific pore volume of Norit DLC Super 50, whereas less active peptides were adsorbed less efficient due to their higher hydrophobicity and did not impact Ile-Trp adsorption. After the adsorption, Ile-Trp was recovered by elution with ethanol. Three protein hydrolysates obtained by different enzyme combinations were mixed with activated carbon and the peptide adsorption was investigated by RP-HPLC. The amount of Trp-containing and ACE-inhibiting short chain peptides decreased selectively in contrast to more polar peptides, but the amount of adsorbed Ile-Trp is smaller than for single component adsorption. © 2014 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20